LITERATURE REVIEW ON WELL-BEING AND RESILIENCE FROM THE PERSPECTIVE OF HUMAN RESOURCE MANAGEMENT - Sa’adin, Izmayani; Wan Mohamad, Wan Maisara; Ahmad, Nursaadatun Nisak; Tuan Kub, Tuan Mohd Nor Hafiz (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
In today’s fast-changing economic landscape, businesses must develop strategic approaches to ensure organizational success and staff retention. As digital transformation and AI-driven innovations workplaces, HR departments play a vital role in fostering well-being and resilience through technology-enabled strategies. Well-being and resilience are two fundamental ideas in Human Resource Management (HRM) that improve the performance of both employees and organizations. The present study evaluates the literature on well-being, resilience, and HRM viewpoints through an analysis of 15 peer-reviewed academic papers. The review is structured into two tables: the first presents article details (title, author, journal, and year of publication), while the second summarizes key findings and recommendations. Two primary findings are highlighted in the study: first, a variety of HR management strategies that are intended to improve individual and organizational performance; and second, the identification of well-being and resilience gaps and how HRM measures can address them. Ultimately, the effectiveness of HRM in improving performance depends on the combined efforts of individuals and organizations, as well as the integration of AI-driven innovations.